Didarchtik’s Final Workshop Butser June 2012 - Roeland P Paardekooper (EXARC Journal)
By mid-2012, the Learning Partnership Didarchtik had come to an end with a last workshop at Butser Ancient Farm in the UK. Many subjects we had touched on over the previous two years were back on the table – just as needed: this was the moment to look back on our experiences and see if we had learned something. Besides wrapping up our experiences, it was an extra-long workshop that including getting to know one of the oldest archaeological open-air museums in the UK.